Arachidonate 15-lipoxygenase type B knockdown leads to reduced lipid accumulation and inflammation in atherosclerosis. - Lisa U Magnusson; Annika Lundqvist; Merja Nurkkala Karlsson; Kristina Skålén; Max Levin; Olov Wiklund; Jan Borén; Lillemor Mattsson Hultén (PLoS ONE, 2012)
Inflammation in the vascular wall is important for development of atherosclerosis. We have shown previously that arachidonate 15-lipoxygenase type B (ALOX15B) is more highly expressed in human atherosclerotic lesions than in healthy arteries. This enzyme oxidizes fatty acids to substances that promote local inflammation and is expressed in lipid-loaded macrophages (foam cells) present in the atherosclerotic lesions. Here, we investigated the role of ALOX15B in foam cell formation in human primary macrophages and found that silencing of human ALOX15B decreased cellular lipid accumulation as well as proinflammatory cytokine secretion from macrophages. To investigate the role of ALOX15B in promoting the development of atherosclerosis in vivo, we used lentiviral shRNA silencing and bone marrow transplantation to knockdown mouse Alox15b gene expression in LDL-receptor-deficient (Ldlr(-/-)) mice. Knockdown of mouse Alox15b in vivo decreased plaque lipid content and markers of inflammation. In summary, we have shown that ALOX15B influences progression of atherosclerosis, indicating that this enzyme has an active proatherogenic role.